2015
DOI: 10.1179/2055075815y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity determinants for dual function catalysts: applied to methanol selective oxidation on iron molybdate

Abstract: Evolution of the IRAS spectrum with temperature after adsorbing methanol at room temperature. The bands at 2930 and 2820 cm 21 are due to the methoxy species C -H stretches, while that at 2870 is due to the formate.Here, we report a simple, quantitative model to describe the behaviour of bi-cationic oxide catalysts, in terms of selectivity variation as a function of increased loading of one cation into a sample of the other. We consider its application to a particular catalytic system, namely the selective oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 20 publications
3
31
1
Order By: Relevance
“…CO production is observed at higher temperatures, reaching its peak at approximately 230 °C; similar behaviour was observed for previous Mobased systems, though formaldehyde production peaks at higher temperatures for MoO x /Fe 2 O 3 [18,19]. It is suggested that isolated cation sites are responsible for CO generation [18,20,24,25]; surface VO x is present in sufficient quantity to preclude multiple neighbouring Fe sites ( : this can be ascribed to the shell-core process, which is known to enhance surface area [18,19].…”
Section: Resultssupporting
confidence: 82%
“…CO production is observed at higher temperatures, reaching its peak at approximately 230 °C; similar behaviour was observed for previous Mobased systems, though formaldehyde production peaks at higher temperatures for MoO x /Fe 2 O 3 [18,19]. It is suggested that isolated cation sites are responsible for CO generation [18,20,24,25]; surface VO x is present in sufficient quantity to preclude multiple neighbouring Fe sites ( : this can be ascribed to the shell-core process, which is known to enhance surface area [18,19].…”
Section: Resultssupporting
confidence: 82%
“…Although widely valued for its efficacy in the reaction, there is a surprising lack of knowledge regarding the catalyst surface layer in Fe 2 (MoO 4 ) 3 , and more importantly how it reacts with the incoming methanol reactant under high pressure conditions. This has been a topic of great interest, with many authors able to identify the phases which are formed through reduction and regeneration of the catalyst [3,[36][37][38], but unable to designate these intermediate phases to a defined reaction mechanism.…”
Section: Initial Investigations Into the Mechanism And Reaction Site mentioning
confidence: 99%
“…A recent paper from our research team reports a simple quantative model to describe the behavior of bi-cationic systems [36], comparing selectivity as a function of Mo loading on Fe2O3 (Figures 19 and 20). Surface doped materials are commended for their use in learning about the active configuration and its relationship to high selectivity.…”
Section: Initial Investigations Into the Mechanism And Reaction Site mentioning
confidence: 99%
“…5 below, and show clear segregation of Mo to the surface of the particle. This has also subsequently been reproduced by high resolution TEM/EDAX analysis [24,25].…”
Section: Rule 3 Preferential Cation Segregation Occurs and Is Crucialmentioning
confidence: 66%
“…What can be seen here is that the catalyst starts operating at very high conversion and selectivity at 250°C, but the conversion drops quickly to *20 % and then more slowly during the course of the experiment, reaching 10 %. The selectivity drops to *50 %, and the main non-selective product is CO, most likely due to the appearance of some Fe in the surface layers [24]. However, the most important point here is that many monolayers equivalent of oxygen can be removed from the lattice, and this can only occur by bulk to surface diffusion.…”
Section: Rule 2 Bulk Oxygen Can Become Active Surface Oxygenmentioning
confidence: 92%